A cost-minimization analysis of diuretic-based antihypertensive therapy reducing cardiovascular events in older adults with isolated systolic hypertension - Chen, G John (BioMed Central, 2005)
BACKGROUND: Hypertension is among the most common chronic condition in middle-aged and older adults. Approximately 50 million Americans are currently diagnosed with this condition, and more than $18.7 billion is spent on hypertension management, including $3.8 billion for medications. There are numerous pharmacological agents that can be chosen to treat hypertension by physicians in clinical practices. The purpose of this study was to assess the cost of alternative antihypertensive treatments in older adults with isolated systolic hypertension (ISH). METHOD: Using the Systolic Hypertension in the Elderly Program (SHEP) and other data, a cost-minimization analysis was performed. The cost was presented as the cost of number-needed-to treat (NNT) of patients for 5 years to prevent one adverse event associated with cardiovascular disease (CVD). RESULT: It was found that the cost of 5 year NNT to prevent one adverse CVD event ranged widely from $6,843 to $37,408 in older patients with ISH. The incremental cost of the 5 year NNT was lower to treat older patients in the very high CVD risk group relative to patients in the lower CVD risk group, ranging from $456 to $15,511. Compared to the cost of the 5 year NNT of other commonly prescribed antihypertensive drugs, the cost of SHEP-based therapy is the lowest. The incremental costs of the 5 year NNT would be higher if other agents were used, ranging from $6,372 to $38,667 to prevent one CVD event relative to SHEP-based drug therapy. CONCLUSION: Antihypertensive therapy that is diuretic-based and that includes either low-dose reserpine or atenolol is an effective and relatively inexpensive strategy to prevent cardiovascular events in older adults with isolated systolic hypertension. Use of the diuretic-based therapy is the most cost-effective in patients at high risk for developing cardiovascular disease.